2011
DOI: 10.3161/00159301ff2011.54.1.087
|View full text |Cite
|
Sign up to set email alerts
|

Common hamster Cricetus cricetus (L., 1758) in the Silesian Voivodeship, South Poland

Abstract: Katarzyna S k o w r o ń s k a -O c h m a n n *, Joanna Z i o m e k ** and Agata B a n a s z e k *** In t r o d u c t i o n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In the analysis of microsatellite diversity in the Polish part of the common hamster range we showed that the Pannonian populations were isolated from one another (Banaszek et al 2011a). However, the recent, detailed inventarization in the Upper Silesia revealed the presence of some more local populations of the common hamster (Skowrońska et al 2011)…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis of microsatellite diversity in the Polish part of the common hamster range we showed that the Pannonian populations were isolated from one another (Banaszek et al 2011a). However, the recent, detailed inventarization in the Upper Silesia revealed the presence of some more local populations of the common hamster (Skowrońska et al 2011)…”
Section: Discussionmentioning
confidence: 99%